2009
DOI: 10.1371/journal.pone.0004518
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Inactivation of p12Cdk2ap1, CDK2 Associating Protein 1, Leads to Early Embryonic Lethality

Abstract: Targeted disruption of murine Cdk2ap1, an inhibitor of CDK2 function and hence G1/S transition, results in the embryonic lethality with a high penetration rate. Detailed timed pregnancy analysis of embryos showed that the lethality occurred between embryonic day 3.5 pc and 5.5 pc, a period of implantation and early development of implanted embryos. Two homozygous knockout mice that survived to term showed identical craniofacial defect, including a short snout and a round forehead. Examination of craniofacial m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…Although this study lacked the population characterization of the previous study (which ruled out contaminant differentiating cells from analysis), its results are consistent with a study showing that the CDK2 inhibitor CDK2-associating protein 1 was required for promoter methylation and down-regulation of Oct4 during differentiation [26]. As this result was obtained in mESCs, this supports a role for CDK2 in controlling pluripotency in mESCs as well as hESCs [27]. …”
Section: The Cell Cycle and The Regulation Of Pluripotencysupporting
confidence: 86%
“…Although this study lacked the population characterization of the previous study (which ruled out contaminant differentiating cells from analysis), its results are consistent with a study showing that the CDK2 inhibitor CDK2-associating protein 1 was required for promoter methylation and down-regulation of Oct4 during differentiation [26]. As this result was obtained in mESCs, this supports a role for CDK2 in controlling pluripotency in mESCs as well as hESCs [27]. …”
Section: The Cell Cycle and The Regulation Of Pluripotencysupporting
confidence: 86%
“…In addition, accumulated evidence has indicated that the expression levels of CDK2AP1 may be used as an indicator in diagnostics for the invasiveness and prognosis of oral squamous cell carcinoma, esophageal squamous cell carcinomas and gastric cancer tissues in humans (10,14). Moreover, a recent study revealed that targeted disruption of murine Cdk2ap1 resulted in embryonic lethality with a high penetration rate, which highlights the essential role of CDK2AP1 in the mammal (22).…”
Section: Discussionmentioning
confidence: 99%
“…Twist 2 knockout mice have severe growth retardation with atrophic dermis, thymus, liver and fat tissues (22). p12 knockout mice died during gestation but two survived mice have been shown to exhibit craniofacial defects with a short snout and a round forehead compared to wild type animals (23). These results indicate that p12 and Twist 2 are linked to EMT and to the maintenance of mesenchymal lineage during embryogenesis.…”
Section: Emt Of Hcpc-1 Cells Induced By P12cdk2-ap1mentioning
confidence: 99%